2000
DOI: 10.1038/80614
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal synaptic potentiation: Delivery of GluR4-containing AMPA receptors by spontaneous activity

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
404
2
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 385 publications
(422 citation statements)
references
References 43 publications
13
404
2
3
Order By: Relevance
“…Interestingly, specific factors secreted from astrocytes directly affect the subunit composition and surface expression of synaptic AMPARs during development (for review see 69 ). It has also been reported that, early in development, GluA4 homomers are preferentially inserted into silent synapses at P5-7 in an activity-and NMDARdependent, but CaMKII-independent manner 12 . These GluA4 homomers are subsequently exchanged for GluA2-containing receptors by a constitutive process that maintains synaptic strength.…”
Section: Subunit Expression During Developmentmentioning
confidence: 90%
See 2 more Smart Citations
“…Interestingly, specific factors secreted from astrocytes directly affect the subunit composition and surface expression of synaptic AMPARs during development (for review see 69 ). It has also been reported that, early in development, GluA4 homomers are preferentially inserted into silent synapses at P5-7 in an activity-and NMDARdependent, but CaMKII-independent manner 12 . These GluA4 homomers are subsequently exchanged for GluA2-containing receptors by a constitutive process that maintains synaptic strength.…”
Section: Subunit Expression During Developmentmentioning
confidence: 90%
“…However, other studies of subunit abundance in rat hippocampus and cortex suggest AMPARs comprise mainly heteromers containing GluA1 and GluA2 or GluA2 and GluA3 [8][9][10] with approximately equivalent amounts of each heteromer complex 11 . GluA4, on the other hand is tightly developmentally regulated and is sparsely expressed at glutamatergic synapses in principal neurons in adult brain 12 . It should be noted, however, that GluA4 is a key determinant of the properties of AMPAR-mediated transmission in interneurons, especially in parvalbumin-containing inhibitory interneurons 13,14 .…”
Section: Subunit-specific Traffickingmentioning
confidence: 99%
See 1 more Smart Citation
“…GluA4-containing AMPAR can also be delivered into the synapse after neuronal conditioning (eg, Mokin and Keifer, 2004) and activity (eg, Zhu et al, 2000). In vitro model of eyeblink classical conditioning, where a weak electrical stimulation of the auditory nerve (the 'tone' CS) is paired with a strong stimulation of the trigeminal nerve (the 'air puff' US), leads to marked increased synaptic delivery of GluA4-containing AMPAR when compared with nonassociative stimulation (random presentations of CS and US) (eg, Mokin and Keifer, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of different AMPAR subunits in CA1 neurons of organotypic hippocampal slice cultures indicates that receptors made of different subunits participate preferentially in various forms of AMPAR insertion. Although GluR2-and GluR3-containing receptors make up the bulk of constitutively recycling AMPARs, GluR1 dominates if receptors are inserted after appropriate NMDAR activation 32,33 . It is interesting to note that subunit-specificity of these interactions might vary from synapse to synapse.…”
Section: Insertion Of Amparsmentioning
confidence: 99%